Radical‐Functionalised Gel: A Building‐Block Strategy for Magnetochiral Assembly. Issue 2 (3rd December 2012) - Mannini, Matteo; Cicchi, Stefano; Berti, Debora; Caneschi, Andrea; Brandi, Alberto; Lascialfari, Luisa; Sorace, Lorenzo
Abstract A chiral organogelating scaffold is functionalised with a stable organic radical pendant. The morphology and spectroscopic properties of the gels are investigated as a function of the organogelator concentration and temperature. The combination of AFM and ESR spectroscopy provides firm evidence that the architecture responsible for the formation of the macroscopic gel (i.e., the fibrillar structure) is maintained below the gelling concentration. This opens relevant perspectives in terms of the realisation of complex supramolecular chiral structures incorporating paramagnetic functions, and demonstrates that the ESR technique is suitable as a fast and direct check of the sample state (gel, solution, or small aggregates).